Peroxisomal dysfunction interferes with odontogenesis and leads to developmentally delayed teeth and defects in distinct dental cells in Pex11b-deficient mice - Colasante, Claudia; Jednakowski, Julia; Valerius, Klaus-Peter; Li, Xiaoling; Baumgart-Vogt, Eveline; Justus Liebig University Giessen (My University, 2024)
Human peroxisomal biogenesis disorders of the Zellweger syndrome spectrum affect skeletal development and induce tooth malformations. Whereas several peroxisomal knockout mouse studies elucidated the pathogenesis of skeletal defects, little information is available on how dental pathologies arise in peroxisomal biogenesis disorder patients. To understand the impact of severe peroxisomal dysfunction on early odontogenesis, here we performed morphometric studies on developing molars of new-born Pex11b knockout mice. Immunofluorescence analysis revealed reduced peroxisome number and mistargeting of the peroxisomal matrix enzyme catalase to the cytoplasm in several dental cell types of the Pex11b knockout animals. We also observed secondary mitochondrial alterations, comprising decreased staining of mitochondrial superoxide dismutase and of complex IV in cells of the developing molar. The peroxisomal defect caused by the PEX11b knockout also decreased the staining of cytokeratin intermediate filaments and of the secretory proteins amelogenin, osteopontin and osteocalcin. Interestingly, the staining of the gap junction protein connexin 43, an important modulator of tissue development, was also decreased, possibly causing the observed cellular disarrangement within the inner enamel epithelium and the odontoblast palisade. Taken together, our results show that the severe phenotype associated with the PEX11b knockout results in a reduction of the number of peroxisomes in dental cells and causes a delay odontogenesis. This adds a new component to the already described symptomatic spectrum induced by severe peroxisomal defects.
Keywords: ddc:610